POLITICAL PARTICIPATION DURING THE COVID PANDEMIC - Diyas Widiyarti; Heri Sunaryanto (Universitas Djuanda Bogor, 2023)
The aims of this study was to identify and analyze the socio-political factors behind the high voter toward the Election of the Governor and Vice Governor of Bengkulu in 2020. This research was a mixed research between quantitative and qualitative method. Using the purposive sampling technique with informants who represent various elements directly related to the Pilkada (Local Distric Heads Election) of Governor and Vice Governor which were held simultaneously in Indonesia. on December 9, 2020. Information collection techniques were carried out using Focus Group Discussion (FGD) and in-depth interviews. The results of the study were analyzed using the Miles and Huberman technique by doing reduction, display, and triangulation. The results of the study showed that there were several socio-politic factors that had a direct contribution to the high voter toward the Election of the Governor and Vice Governor of Bengkulu Province in 2020 (77.68 percent). These factors were transactional politics (money politics), the role of the media, the role of General Election Commission (Komisi Pemilihan Umum-KPU) and General Election Supervisory Agency (Badan Pengawas Pemilu-Bawaslu), the role of candidates and the pattern of visiting campaigns. The conclusion of the study is that there is no single factor that dominantly affects voter participation in the Bengkulu Governor and Vice Governor Elections. Voter participation is a product of the interdependence of various social and political factors.